2021
DOI: 10.1080/16549716.2021.1883911
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening prevention of nutrition-related non-communicable diseases through sugar-sweetened beverages tax in Rwanda: a policy landscape analysis

Abstract: Background : Food and beverages high in sugar are recognized to be among the major risk factors for nutrition-related non-communicable diseases. The growing presence of ultra-processed food producers has resulted in shifts to diets that are associated with non-communicable diseases and which include sugar-sweetened beverages. Sugar-sweetened beverage taxation presents an opportunity to prevent non-communicable diseases but it comes with challenges. Objectives : To describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…While stakeholders in our study were generally supportive of health taxes through the presence of an enabling environment (ongoing stakeholder discussions for tobacco tax review) and global or regional momentum (by the Economic Community of West African States and the United Nations Development Programme), a strong industry presence (mainly alcohol and SSBs) was observed. Similar to countries such as Uganda54 and Rwanda,55 perceived tensions exist between health and economic policies. Nevertheless, despite industry efforts and existing tension within ministries, taxation is gaining more attention from policy makers as a win–win–win policy measure for public health, domestic resource mobilisation and equity (although contested) 36…”
Section: Discussionmentioning
confidence: 99%
“…While stakeholders in our study were generally supportive of health taxes through the presence of an enabling environment (ongoing stakeholder discussions for tobacco tax review) and global or regional momentum (by the Economic Community of West African States and the United Nations Development Programme), a strong industry presence (mainly alcohol and SSBs) was observed. Similar to countries such as Uganda54 and Rwanda,55 perceived tensions exist between health and economic policies. Nevertheless, despite industry efforts and existing tension within ministries, taxation is gaining more attention from policy makers as a win–win–win policy measure for public health, domestic resource mobilisation and equity (although contested) 36…”
Section: Discussionmentioning
confidence: 99%
“…Out of the total, 11(25.6%) [ 24 34 ] originated from Western Africa only, 11(25.6%) [ 35 45 ] from Southern Africa only, 11(25.6%) [ 46 56 ] from Eastern Africa only and 3(7.1%) [ 57 59 ] from Eastern and Southern Africa. Also, 1(2.3%) [ 60 ] from Northern only, 1(2.3%) [ 61 ] from Central only, 1(2.3%) [ 62 ] from Eastern and Western, 1(2.3%) [ 63 ] from Western and Northern, 1(2.3%) [ 64 ] from Western and Southern, 1(2.3%) [ 65 ] from Central, Eastern, Western and Southern, and 1(2.3%) [ 66 ], thus, cutting across the entire continent. The approaches adopted by these articles included quantitative 2(4.5%) [ 39 , 66 ], qualitative 39(91%) [ 24 32 , 35 38 , 40 51 , 53 65 ] and mixed method 2(4.5%) [ 33 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study identified low awareness on the motives of the levy, and were influenced by addiction and branding effect to purchase SSB 36,37 . Moreover, implementation of taxation in sugar based on sugar content might counteract this effect 38 …”
Section: Economic Priorities Over Population Healthmentioning
confidence: 94%
“…36,37 Moreover, implementation of taxation in sugar based on sugar content might counteract this effect. 38 The introduction of taxation that can have a positive effect on the public health faces challenges due to the conflict of interest from government authorities and different globalization stakeholders. 39,40 This is mainly due to lack of common understanding or agreement of the purpose or goal of taxation imposed to these products.…”
Section: Economic Priorities Over Population Healthmentioning
confidence: 99%